2010
DOI: 10.1016/j.chom.2010.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Polyomavirus and Two Previously Unknown Polyomaviruses Are Chronically Shed from Human Skin

Abstract: Summary Mounting evidence supports the concept that Merkel cell polyomavirus (MCV) is a causal factor underlying most cases of a highly lethal form of skin cancer known as Merkel cell carcinoma. To explore the possibility that polyomaviruses commonly infect healthy human skin, we developed an improved rolling circle amplification (RCA) technique to isolate circular DNA viral genomes from skin swab specimens. Complete MCV genomes were recovered from 14/35 (40%) healthy adults, providing the first full-length, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
603
3
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 512 publications
(630 citation statements)
references
References 40 publications
17
603
3
7
Order By: Relevance
“…182 Polyomaviruses also represent an emerging group of viruses requiring study because of their potential to cause epithelial malignancy. 183 The recently described Merkel cell skin cancer occurring in immune deficient states is driven by the Merkel cell polyomavirus, which is closely related to BK and JC viruses, both of which reactivate after HCT. 184 …”
Section: Non-transplant-related Risk Factorsmentioning
confidence: 99%
“…182 Polyomaviruses also represent an emerging group of viruses requiring study because of their potential to cause epithelial malignancy. 183 The recently described Merkel cell skin cancer occurring in immune deficient states is driven by the Merkel cell polyomavirus, which is closely related to BK and JC viruses, both of which reactivate after HCT. 184 …”
Section: Non-transplant-related Risk Factorsmentioning
confidence: 99%
“…For example, the KI and WU polyomaviruses were characterized from patients with respiratory tract infections, although their role as a causative agent has not yet been confirmed (Allander et al, 2007;Gaynor et al, 2007). Merkel cell polyomavirus (MCPyV) was found to be specifically linked to Merkel cell carcinoma (MCC), a rare but aggressive form of skin cancer of neuroendocrine origin (Feng et al, 2008 polyomavirus-6 (HPyV6) and HPyV7, in addition to MCPyV, were identified from healthy human skin swabs (Schowalter et al, 2010). As for non-human polyomaviruses, most of these were identified as cell culture contaminants, from cell-free preparations or in laboratory animals.…”
Section: Introductionmentioning
confidence: 99%
“…At present, eight human and 18 non-human polyomaviruses are known (Groenewoud et al, 2010;Krumbholz et al, 2009;Misra et al, 2009;Schowalter et al, 2010;van der Meijden et al, 2010). Most mammalian polyomaviruses cause subclinical infections with life-long persistence in their natural immunocompetent hosts.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only two groups have reported phylogenetic analyses of MCPyV using the full-length LT gene and complete viral sequences. Schowalter et al (2010) raised the possibility that different MCPyV strains may be prevalent in Asia. However, their study sampled a small group of healthy individuals residing in the USA, and only three MCPyV genomes were isolated from skin swabs of three healthy individuals born in Asia: strains 10b (GenBank accession no.…”
mentioning
confidence: 99%
“…First, phylogenetic studies were performed using 82 complete sequences of the MCPyV LT gene, comprising our 12 Japanese tumour-derived sequences and four previously reported sequences derived from individuals born in Asia (strains 10b, 13a, 16b and TKS) (Katano et al, 2009;Schowalter et al, 2010), and 66 Caucasian strains retrieved from GenBank in August 2013. According to the phylogenetic tree (Fig.…”
mentioning
confidence: 99%